Flux Switching Permanent Magnet Motor using Segmented Outer Rotor Structure for Electric Scooter - Enwelum Mbadiwe I; Erwan Sulaiman (Institute of Advanced Engineering and Science, 2017)
Flux switching motor is a type of electric machine that locates both flux source and armature windings on the stator leaving its rotor a simple piece of iron. This machine was developed by combining the toothed stator structure of induction machine and the toothed rotor structure of switched reluctance machine together. Furthermore, it has three types of flux sources which include permanent magnet. Conventionally, the toothed kind of rotor has dominated machines rotor design and has been known for high manufacturing cost and iron loss, resulting to low performance. This calls for worry and the need to overcome it and also reduce the manufacturing cost while securing high torque. This paper presents flux switching permanent magnet motor employing segmented outer rotor for high torque capability. 2D-FEA using JMAG to investigate the motor characteristics in terms of flux linkage, Induce back-emf, cogging torque, maximum average torque and efficiency. Finally, preliminary results and comparison revealed that motors employing segmented rotor are capable of higher torque than conventional toothed rotor.